Quality of concept maps is affected by map building strategies. Issue 1 (1st August 2020) - Srivastava, Anveshna; Srivastava, Nisheeth; Chandrasekharan, Sanjay
Abstract: Concept‐maps are widely used to assess students' conceptual understanding in different subject areas. Conventionally, it is mostly built maps which are assessed. In this study, we explore if "concept‐mapping" could be used as a case for constructive alignment of both the process and the outcome of learning. Specifically, we have studied how a simple measure of looking at the order in which concept map elements‐concepts (cards, C), links (arrows, A), and linking phrases (phrases, P)‐ are placed on the working space reveals information about the quality of the final generated map. We report findings from analysis of the concept‐mapping process in two separate groups of university students ( N = 38 (18 + 20)) who were asked, individually, to build concept maps related to two separate concepts in biology and chemistry respectively. We found that, across both groups, students consistently followed the same order of element placement that they began with and found significant differences in the quality of eventual maps resulting from students' map building strategies. Our results suggest that the quality of students' concept maps depends considerably on the strategy used to build it, and point to the supplementary role that the physical working space of the concept‐mapping exercise offers to students' own working memory as a possible explanation for these quality differences.